IMPACT OF HEART ANATOMY ON TESTS THAT ASSESS CARDIOVASCULAR DISEASES (CIPEEX, 2025)
Cardiovascular diseases are the leading cause of death worldwide, requiring accurate diagnostic methods for early detection, monitoring, and prevention of complications. Tests such as echocardiography, cardiac magnetic resonance imaging (CMR), and coronary angiography are essential. However, cardiac anatomical variations can interfere with the accuracy of these tests, compromising diagnosis.